224k views
3 votes
Fiona solved the equation shown 1/2-1/3(6x-3)=-13/2 what is the missing step of her solution?

Fiona solved the equation shown 1/2-1/3(6x-3)=-13/2 what is the missing step of her-example-1
User Kurama
by
4.5k points

2 Answers

1 vote

Answer:

Simplify by combining like terms

Explanation:

User Mitul Goti
by
4.6k points
2 votes

Answer:

Summation of the non variable Expression within the quality sign

1/2 + 1-2x= -13/2

3/2-2x= -13/2

Explanation:

1/2-1/3(6x-3)=-13/2

First step

Using the distributive property to simply

1/2-(6x/3)+(3/3)=-13/2

1/2 -2x +1 = -13/2

Second step

Summation of the non variable Expression within the quality sign

1/2 + 1-2x= -13/2

3/2-2x= -13/2

Third step

Isolating the variable Expression by using the addition property of equality

-2x = -13/2 - 3/2

-2x = -16/2

Fourth step

Isolating the variable by using the division property of equality

-2x = -16/2

X = -16/2 * -1/2

X = -16/-4

X= 4

User Merlin Mason
by
5.0k points